THE POLICE POWER OF THE ELECTORAL JUSTICE AND THE GUARANTEE OF THE NORMALITY OF ELECTIONS (CIPEEX, 2025)
The Electoral Justice, as a specialized branch of the Judiciary, plays a pivotal role in safeguarding the legitimacy and integrity of the electoral process through the exercise of its regulatory and supervisory authority, commonly referred to as police power. This prerogative manifests in its capacity to oversee and regulate electoral propaganda, the use of public assets and services, the conduct of public officials, as well as other practices that may compromise equality among candidates. The present study seeks to examine the concept, scope, and limitations of the Electoral Justice’s police power, elucidating how its enforcement contributes to the transparency and fairness of elections. The analysis encompasses relevant judicial decisions, applicable legislation, and doctrinal perspectives, thereby highlighting both the challenges and the effectiveness of the preventive and repressive measures adopted by the Electoral Justice. It concludes that, notwithstanding criticisms concerning the breadth of discretion afforded to the institution, police power constitutes an indispensable mechanism for ensuring the regularity of elections and upholding democratic principles.
Keywords: Electoral Justice; Elections; Legality; Equality; Police power